Unlocking efficient water splitting through Fe-induced activity enhancement in NiCo2O4 bifunctional electrocatalysts - Sankar, K. N. Amba; Mahana, Debashrita; Mohan, S.; Gupta, Suryakant B.; Hussain, Amreen A. (Journal of Materials Science, 2026)
The development of efficient, durable and inexpensive bifunctional electrocatalysts is essential for advancing overall water splitting technologies. In this study, we present a novel strategy involving dilute Fe doping in NiCo2O4 (NCO) spinel structures to enhance their electrocatalytic activity and stability. Fe was introduced at varying concentrations, and the resulting Fe-doped NCO catalysts were systematically characterized to understand their structural, morphological, and surface properties. Comprehensive structural and surface analyses revealed the successful incorporation of Fe ions into the NCO lattice without altering its intrinsic spinel framework. Brunauer-Emmett-Teller (BET) analysis showed that the NCO-Fe1 sample exhibited the highest surface area (41.82 m2g-1) and the smallest pore size, facilitating enhanced ion diffusion and exposure of active sites. Electrochemical studies revealed a pronounced improvement in bifunctional catalytic activity for the NCO-Fe1 catalyst, which delivered low overpotentials of 228 mV for the hydrogen evolution reaction (HER) and 274 mV for the oxygen evolution reaction (OER) at 10 mAcm-2. The corresponding Tafel slopes of 151 mVdec-1 (HER) and 52.54 mVdec-1 (OER) indicate favourable reaction kinetics and efficient charge-transfer dynamics. Furthermore, the overall water-splitting device constructed using NCO-Fe1 electrodes required only 1.72 V at 10 mAcm-2 to sustain continuous operation, maintaining excellent durability over 300 h of testing without significant performance degradation. Hence, this study provides new insights into the role of dilute dopant engineering in multicomponent oxides and establishes NCO-Fe1 as a promising, high-performance, and durable bifunctional electrocatalyst for sustainable water-splitting applications.